2009
DOI: 10.1007/s10557-009-6210-7
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Inhibits Fractalkine Expression in Atherosclerotic Plaques and Reduces Atherosclerosis in ApoE Gene Knockout Mice

Abstract: The results of our study indicate that high dose aspirin can improve the atherosclerotic lesion and suppress the fractalkine expression in murine aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 24 publications
1
18
0
3
Order By: Relevance
“…These effects were associated with a marked and additive 90% reduction in atherosclerosis [28] . More recently, Liu et al, using both RT-PCR and immunohistochemical analysis, showed that CX3CL1 expression was higher in high-fat-vs normal diet-fed ApoE gene knockout mice and was significantly decreased by aspirin treatment [29] . Recent studies have also implicated CX3CL1 in platelet stimulation and activation.…”
Section: Wwwchinapharcom Apostolakis S Et Almentioning
confidence: 99%
“…These effects were associated with a marked and additive 90% reduction in atherosclerosis [28] . More recently, Liu et al, using both RT-PCR and immunohistochemical analysis, showed that CX3CL1 expression was higher in high-fat-vs normal diet-fed ApoE gene knockout mice and was significantly decreased by aspirin treatment [29] . Recent studies have also implicated CX3CL1 in platelet stimulation and activation.…”
Section: Wwwchinapharcom Apostolakis S Et Almentioning
confidence: 99%
“…Доведено, що при хронічних запальних захворюваннях актива-ція експресії фракталкіну відіграє негативну роль, а при патологічних станах, пов'язаних з імунною недостатністю, навпаки, -позитивну. Є дані, що підвищення експресії фракталкіну корелює з кра-щим прогнозом у пацієнтів з аденокарциномою шлунка [13].…”
Section: вступunclassified
“…У світі проведено декілька досліджень щодо взаємозв'язку між рівнями сироваткового фракталкіну та серцево-судинною патологією [27][28][29][30][31], кластерину і складовими метаболічного синдрому [32][33][34]. Однак, їх результати є досить суперечливими, що пояснюється значними розбіжностями у когортах осіб, яких було обстежено.…”
Section: вступunclassified